Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Sedimentary characteristics and palaeo-ocean environment evolution of the Hejiazhai Formation in the early Tonian Period, Western Henan - Boyang Xu; Deshun Zheng; Qianqian Li; Sha Ren; Fengbo Sun; Jiaqi Fu; Xin Wang; Wentong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Recent advances in spinel nickel cobalt oxide-based nanostructures for oxygen electrocatalysis - He Li; Sha Qiao; Kai Fu; Liang Zhang; Jun Wang (Fuel, 2026)

A ceRNA axis of lncRNA MSTRG.14394.1/miR-144-3p/NR1H3 responds to diverse bacterial PAMPs in teleost fish - Yishuai Li; Mengyang Chang; Suxu Tan; Wenwen Wang; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Qingyang Fu; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Genome-wide insights into the regulatory networks of ZmHsf28 in salt and drought stress - Lijun Liu; Xia Zheng; Xiaoyu Sha; Shuaibing Tian; Ziyi Luo; Yuhan Zhang; Guocheng Wei; Yuxin Li; Jingye Fu; Qiang Wang (Plant Science, 2026)

Volcanic rock-confined core-shell nanoreactors as a highly effective and recyclable peroxymonosulfate activator for levofloxacin degradation: Performance, mechanism, and ecotoxicity assessment - Xinxi Fu; Xiangyu Li; Yang Zhong; Shuai Shao; Yonghua Chen; Sha Xie (Environmental Research, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Covalently grafted pyrenoviologen on nano-SiO2 for ultrasensitive fluorescent detection of picric acid - Yiting Wang; Ni Yan; Yawen Li; Jiayao Sha; Yao Liu; Tianle Cao; Tianyue Yuan; Wenjie Ni; Weiqiao Wang; Jiuxu Fu; Gang He (Chemical Engineering Journal, 2026)

V-ATPase B mediates Bt Cry1Ac binding and toxicity in Grapholita molesta - Dandan Pan; Jiayang Feng; Jiacheng Ye; Xiaoyan Yang; Xiaoyan Zhang; Xiaofang Sha; Donghan Wang; Yanshen Fu; Chunxiao Men; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

ATP synthase subunit γ mediates Cry1Ac binding and toxicity in Grapholita molesta - Jiayang Feng; Dandan Pan; Yichen Wang; Xiaoyan Zhang; Xiaofang Sha; Yanshen Fu; Jiacheng Ye; Donghan Wang; Xiangqun Yuan; Yiping Li (Pesticide Biochemistry and Physiology, 2025)

The protein kinase MLOP1 mediates pectin fragment signaling and feedback regulation of cell wall synthesis - Xiaohui Liu; Jingjing Sha; Qingyao Li; Shuai Yuan; Jialin Tao; Shihan Fu; Pu Gan; Qiuyan Lan; Johannes Liesche; Chaowen Xiao (Journal of Plant Physiology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Study on the functional role and tissue localization of GmolTrypsin in larvae of Grapholita molesta feeding on different host plants - Dongbiao Lü; Dandan Pan; Donghan Wang; Jiacheng Ye; Xiaofang Sha; Xiaoyan Zhang; Yanshen Fu; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Rapid degradation of frozen soil environments in thermokarst-affected alpine grasslands on the Qinghai-Tibet Plateau under climate change - Yuanhong Deng; Xiaoyan Li; Chao Yang; Fangzhong Shi; Shaojie Zhao; Sha Zhou; Chiyuan Miao; Ruiqiang Ding; Yongshuo H. Fu; Xiaofan Yang; Zhigang Wang (CATENA, 2025)

Achieving efficient phosphorescence of carbon dots via a synergistic enhancement strategy for bright field anti-counterfeiting - Jing Tan; Daiqi Yang; Chunyi Lu; Yi Li; Xingyu Gu; Peng Sha; Songnan Qu; Xin Wang; Lipei Fu; Qijun Li (Chemical Engineering Journal, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

PBAT biodegradable microplastics enhanced organic matter decomposition capacity and CO2 emission in soils with and without straw residue - Sha Chang; Chao Chen; Qing-Long Fu; Aoyu Zhou; Zhuyao Hua; Fengxiao Zhu; Shiyin Li; Huan He (Journal of Hazardous Materials, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Understanding how microbial electrolysis cell assisted anaerobic digestion enhances triclocarban dechlorination in sludge - Sha Long; Qizi Fu; Zhixiang Hao; Luyang Sun; Zihan Li; Yike Guo; Xuran Liu; Fengming Song; Dongbo Wang; Wenming Wang (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Revealing an unrecognized role of free ammonia in sulfur transformation during sludge anaerobic treatment - Qizi Fu; Sha Long; Yunhao Xu; Yan Wang; Bentao Yang; Dandan He; Xuemei Li; Xuran Liu; Qi Lu; Dongbo Wang (Journal of Hazardous Materials, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Global assessment of nature’s contributions to people - Yanxu Liu; Bojie Fu; Shuai Wang; Jonathan R. Rhodes; Yan Li; Wenwu Zhao; Changjia Li; Sha Zhou; Chenxu Wang (Science Bulletin, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

A comprehensive review on coupled processes and mechanisms of soil-vegetation-hydrology, and recent research advances - Zhongkai Li; Xiaoyan Li; Sha Zhou; Xiaofan Yang; Yongshuo Fu; Chiyuan Miao; Shuai Wang; Guanghui Zhang; Xiuchen Wu; Chao Yang; Yuanhong Deng (Science China Earth Sciences, 2022)

Notch1 down-regulation in lineage-restricted niches is involved in the development of mouse eccrine sweat glands - Yuzhen Wang; Bin Yao; Xianlan Duan; Jianjun Li; Wei Song; Enhejirigala; Zhao Li; Xingyu Yuan; Yi Kong; Yijie Zhang; Xiaobing Fu; Sha Huang (Journal of Molecular Histology, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Identifying common genome-wide risk genes for major psychiatric traits - Sha Liu; Shuquan Rao; Yong Xu; Jun Li; Hailiang Huang; Xu Zhang; Hui Fu; Qiang Wang; Hongbao Cao; Ancha Baranova; Chunhui Jin; Fuquan Zhang (Human Genetics, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

PM2.5 affects establishment of immune tolerance in newborn mice by reducing PD-L1 expression - Li Yan; Caihui Gong; Linyan Ying; Wenlong Fu; Sha Liu; Jihong Dai; Zhou Fu (Journal of Biosciences, 2019)

Photosynthetic acclimation of an evergreen broadleaved shrub (Ammopiptanthus mongolicus) to seasonal climate extremes on the Alxa Plateau, a cold desert ecosystem - Zhengzhen Li; Ximeng Li; Kennedy F. Rubert-Nason; Qiong Yang; Qiang Fu; Jinchao Feng; Sha Shi (Trees, 2018)

Effects of dietary fresh fermented soybean meal on growth performance, ammonia and particulate matter emissions, and nitrogen excretion in nursery piglets - Sai-sai Cheng; Yuan Li; Shi-jie Geng; Luan-sha Hu; Xiong-feng Fu; Xin-yan Han (Journal of Zhejiang University-SCIENCE B, 2017)

Effect of tidal stress on fault nucleation and failure of the 2007 M s6.4 Ning’er earthquake - ChaoDi Xie; XingLin Lei; XiaoPing Wu; Hong Fu; ZiYao Xiong; XiongLin Hu; Sha Li (Science China Earth Sciences, 2016)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Late Triassic bivalves associated with a hydrothermal vent system in the Yidun Island Arc (SW China) of the eastern Tethys - Li Lin; LiDong Zhu; YanChun Pang; JinGeng Sha; Franz T. Fürsich; XiuGen Fu; XinLi Wang (Science China Earth Sciences, 2011)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)